SUSTAINED RELEASE BIODEGRADABLE RESIN COMPOSITION CONTAINING PERFUME - FUJIWARA YASUO; HONGO HIDEYUKI; HORI YASUSHI; ABE SEIICHI; HANADA MINORU (1999)
PROBLEM TO BE SOLVED: To obtain the subject composition capable of gradually releasing a smell over a long time and capable of being utilized as an aromatic agent, a deodorizer or the like in response to the characteristics of a perfume by including a biodegradable resin comprising a specific random or block copolyester and the perfume. SOLUTION: This composition comprises (A) a biodegradable resin comprising a random or block copolyester of the formula [R is a 1-15C hydrocarbon group; (m) and (n) are each 0 or 100-9,000; (m)+(n)=200 to 10,000; when (m) and (n) are each not 0, the molar ratio of structural units [I]/[II] is (1-99)/(99-1)] having a number-average mol.wt. of 5,000-1,000,000, and (B) a perfume (e.g. rose oxide). The component A is obtained by subjecting optically active β-butyrolactone and a cyclic carbonate to a successive ring-opening copolymerization in the presence of a catalyst.